SYNTHESIS OF METALLOCOMPLEXES OF SCHIFF BASES AND THEIR STRUCTURAL ANALYSIS - Khakberdiyev Shukhrat Mahramovich; Mamatova Farangiz Qodir qizi (Scholar Express Journals, 2022)
Physicochemical properties of gossypol, their Schiff bases and metallocomplexes were synthesized. When synthesizing derivatives of Schiff's bases, gossypol and primary chiamine are taken in a 1:2 mol ratio, enough 96 % ethyl alcohol is poured for its dissolution and stirred for three hours while heated in a magnetic stirrer. The structure of all obtained substances was analyzed using IR and UV spectra
Keywords: Gossypol; amino compound, Schiff's base; spectrum; biologically active substance